A Good Turn Deserves Another: Political Stability, Corruption and Corruption-Control - Simplice A. Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
We build on existing literature and contemporary challenges to African development to assess the role of political stability in fighting corruption and boosting corruption-control in 53 African countries for the period 1996-2010. We postulate that on the one hand, an atmosphere of political instability should increase the confidence of impunity owing to less corruption-control. On the other hand, in the absence such impunity from corruption, political instability further fuels corruption. Our findings validate both hypotheses. Hence, contrary to a stream of the literature, we establish causal evidence of a positive (negative) nexus between political stability/no violence and corruption-control (corruption). The empirical evidence is based on Generalized Methods of Moments. The findings are robust to contemporary and non-contemporary quantile regressions. The political stability estimates are consistently significant with decreasing (increasing) magnitudes throughout the conditional distributions of corruption (corruption-control). In other words, the positive responsiveness of corruption-control to political stability is an increasing function of corruption-control while the negative responsiveness of corruption to political stability is a decreasing function of corruption. Simply put: a good turn deserves another.
Keywords: F52; K42; O17; O55; P16; 330; Fragility; Corruption; Conflicts; Africa